Common Factors Associated with Osteonecrosis of the Femoral Head in Young Patients Requiring Total Hip Arthroplasty. Issue 3 (May 2015) - Swarup, Ishaan; Lee, Yuo-yu; Movilla, Peter; Figgie, Mark P.
Osteonecrosis of the femoral head is a pathologic condition that commonly affects young patients and requires treatment with total hip arthroplasty (THA). The most common factors associated with osteonecrosis in young patients have not been previously described in the literature. A retrospective study was conducted to describe the most common factors associated with osteonecrosis in patients aged 35 or younger requiring a primary THA. This study included 235 patients and found that the most common factor associated with osteonecrosis was corticosteroid use (61%), followed by idiopathic causes (11%), trauma (9%), other causes (8%), haemoglobinopathies (7%), and alcoholism (3%). There was no significant difference in age between risk groups (p-value = 0.35), however there were significant differences in sex (p-value = 0.02) and unilateral versus bilateral surgery (p-value<0.01). Several factors are associated with the development of osteonecrosis of the femoral head in young patients, and these factors should be given consideration in determining disease aetiology and counselling patients.